Pengaruh Kualitas Tenaga Kerja, Bantuan Modal Usaha dan Teknologi Terhadap Produktivitas Kerja Usaha Mikro Kecil dan Menengah di Jimabaran - Ariani, Duti; Suresmiathi, A.A Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
This study intends to determine the factors that affect labor productivity af micro, small and medium enterprises. Research was conducted in the village of Jimbaran. Study sample totaled 38 micro, small and medium chosen at random and based approach Slovin and Stratified Random Sampling method. Technical analysis used the multiple liniear regression. The result showed that the factors that effect work productivity of micro, small and medium enterprises in Jimbaran is the quality of labor, capital and technology assistance.
Keywords: micro; small and medium enterprises; labor productivity